Analisis Penggunaan Body Care pada Laki-Laki - Nisa, Azatul Khairun; Aisyah, Siti; Murni, Ayda; Saputra, Indra (Lembaga Yasin AlSys, 2025)
Body care has become an increasingly prominent concern among modern men, not only in relation to physical appearance but also as part of a broader effort to maintain overall health and well-being. This study aims to explore male perceptions and usage patterns of body care products in Indonesia. Employing a quantitative approach, data were collected through a survey of 28 respondents representing a range of ages and social backgrounds. The findings reveal that the majority of participants have used body care products over an extended period and possess a basic understanding of their functions. However, challenges remain in selecting products suited to specific skin types and in maintaining consistent usage. Additionally, most respondents expressed a positive attitude toward skincare, demonstrating high levels of self-confidence and indifference toward social stigma. This study offers valuable insights into male consumer behavior regarding body care in Indonesia, which may inform the development of more targeted marketing strategies and educational initiatives.